A 60-year historical record of polycyclic aromatic hydrocarbons (PAHs) pollution in lake sediment from Guangxi Province, Southern China. (December 2018) - Chang, Jie; Zhang, Enlou; Liu, Enfeng; Liu, Huiji; Yang, Xiaoqiang
Highlights: Historical changes of PAH concentrations were reconstructed over the last 60 years. The sources of PAHs in sediment core were identified and discussed. PAH concentrations reached peak values in the 1950s and 1980–1990 s, respectively. The PAH peaks correspond well with regional socio-economic development history. Abstract: Polycyclic aromatic hydrocarbons (PAHs) are toxic organic pollutants which present and persist ubiquitously in the natural environment. We present a sedimentary record of the 16 priority PAHs pollutants from Lake Baxian, a small freshwater lake in a remote area of southern China, spanning the last ca. 60 years. The concentration of PAHs in the sediment (ranging from 1639 to 8766 ng/g) was much higher than the lakes from the remote plateau, western and northwestern China, and of a similarly high level to the lowland urban sites. The sources of PAHs compounds recorded in the sediment were generally derived from petroleum, biomass burning (grass, wood) and high temperature industrial combustion processes. The PAHs were mainly transported to the site from the surrounding regions by atmospheric deposition instead of direct discharge. There were two periods represented by high levels of PAHs: we linked the 1950s peak to the beginning of regional industrial development under the first 'Five-Year-Plan (1951–1955)' policy followed by the founding of the People's Republic of China, while the 1980–1990 s PAHs peak were primarily related to the industrial reboot under the 'Reform and Opening-up' policy (since 1978). Until recently, the ecosystem biodiversity risks imposed by the high level of atmospheric deposited PAHs into remote lowland aquatic systems have been poorly assessed and understood. Our study highlights the importance of investigating the historical total PAHs concentration changes, sources and deposition processes from such systems. Results of this study will provide baseline information to frame management strategies for similar lake systems worldwide.